Single- and Dual-Wavelength Passively Mode-Locked Erbium-Doped Fiber Laser Based on Antimonene Saturable Absorber - Guowei Liu; Fang Zhang; Tiange Wu; Zongwen Li; Wenfei Zhang; Kezhen Han; Fei Xing; Zhongsheng Man; Xiaolu Ge; Shenggui Fu (IEEE Photonics Journal)
As the cousin of phosphorene, antimonene, i.e., two-dimensional Sb monolayer, aroused an intensive attention to its physical performance in recent years. In this paper, few-layer antimonene (FLA) nanosheets with thickness of 3∼6 nm were prepared by liquid phase exfoliation (LPE). The saturated absorption properties were measured using the Z-scan method. The single-and dual-wavelength mode-locked fiber lasers were demonstrated using erbium-doped fiber as a gain medium based on the antimonene saturable absorber. For the single-wavelength pattern, the pulse width of fundamental frequency was 1.73 ns with a frequency of 2.16 MHz. The maximal output power was 7.28 mW, corresponding to the maximal peak power of 1.92 W. In addition, the shortest pulse width of 953 ps was achieved with the high-order mode-locked laser. For the dual-wavelength laser, the two synchronous wavelengths at steady operation were 1561.3 and 1562.7 nm. The difference frequency of these two wavelengths (0.17 × 1012 Hz) belongs to the terahertz waveband, which provides a powerful light source for the development of terahertz. Our results demonstrated that antimonene was an excellent nonlinear absorption material in mode-locked fiber laser and broadened this application in optics.